2016
DOI: 10.1097/scs.0000000000002463
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Necrosis of Upper Lip, and All Fingers and Toes After Norepinephrine Use

Abstract: A 68-year-old woman with necrosis of total finger, toe, and upper lip was requested by department of internal medicine. She was diagnosed with septic shock and treated with norepinephrine 10 days ago. Norepinephrine is an often-used medicine for normalizing blood pressure in septic shock patients. Norepinephrine stimulates adrenergic receptors, causing vasoconstriction and the rise of blood pressure. These peripheral vasoconstrictions sometimes lead to ischemic changes in end organs. In this case report, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
1
14
0
5
Order By: Relevance
“…There are limited reports of extremity ischemia as sequelae of vasopressor use in the setting of sepsis. 2 , 5 , 6 In our experience, a multidisciplinary approach with careful planning leads to successful functional outcome. Awaiting demarcation, staging surgical interventions, HBOT, and NPWT are critical for successful free tissue transfer.…”
Section: Discussionmentioning
confidence: 69%
“…There are limited reports of extremity ischemia as sequelae of vasopressor use in the setting of sepsis. 2 , 5 , 6 In our experience, a multidisciplinary approach with careful planning leads to successful functional outcome. Awaiting demarcation, staging surgical interventions, HBOT, and NPWT are critical for successful free tissue transfer.…”
Section: Discussionmentioning
confidence: 69%
“…5 This theory is supported by histopathological studies, which showed small vessel constriction when intraluminal pressure drops below the critical value of 36-60 mm Hg. 6,7 Several conditions may induce the development of this pathology, including sepsis (bacterial, viral and parasitic), cardiovascular (cardiac failure, hypovolemic shock, pulmonary embolism, supraventricular tachycardia), drugs, neoplastic conditions, and others.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque la norepinefrina es un medicamento eficaz para aumentar la presión arterial, mediante la estimulación de estas 2 vías, su uso excesivo conlleva un riesgo peligroso de isquemia periférica, además de otras complicaciones (hipertensión severa, cefalea intensa, palidez, sudoración severa, entre otras) 3 . La dosis óptima de norepinefrina es de 0,2 a 1,3 mcg / kg / min, para reducir la incidencia de necrosis isquémica de los órganos más distales 8 . En esta paciente, sin embargo, fue necesaria la administración a mayores dosis de norepinefrina (2-3 mcg / kg / min).…”
Section: Discussionunclassified